2013
DOI: 10.1021/jm400731m
|View full text |Cite
|
Sign up to set email alerts
|

Benzazepinones and Benzoxazepinones as Antagonists of Inhibitor of Apoptosis Proteins (IAPs) Selective for the Second Baculovirus IAP Repeat (BIR2) Domain

Abstract: XIAP is a key regulator of apoptosis, and its overexpression in cancer cells may contribute to their survival. The antiapoptotic function of XIAP derives from its BIR domains, which bind to and inhibit pro-apoptotic caspases. Most known IAP inhibitors are selective for the BIR3 domain and bind to cIAP1 and cIAP2 as well as XIAP. Pathways activated upon cIAP binding contribute to the function of these compounds. Inhibitors selective for XIAP should exert pro-apoptotic effects through competition with the termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The compounds that scored best were then synthesised and tested for the ability to abrogate the protein interaction. Although the compounds were only modestly potent 135,136 Such inhibitors are anticipated to have different pharmacodynamics profiles to the less selective compounds.…”
Section: Xiap-smacmentioning
confidence: 99%
“…The compounds that scored best were then synthesised and tested for the ability to abrogate the protein interaction. Although the compounds were only modestly potent 135,136 Such inhibitors are anticipated to have different pharmacodynamics profiles to the less selective compounds.…”
Section: Xiap-smacmentioning
confidence: 99%
“…As a result, bulky and flat chemical groups (like phenylhydrazine or 1-naphthyl moieties) appear to be better suited for the shallow CBC, enhancing both BIR2 affinity and selectivity [ 95 ]. In the last years, through a structure-based approach, novel XIAP-directed compounds were developed [ 96 , 97 ] by exploiting the increased selectivity for the BIR2 domain of XIAP compared to the BIR3 of XIAP and cIAP1. These compounds were shown to promote apoptosis without inducing cIAP1 degradation [ 98 ].…”
Section: Structure and Function Of Birs: The Ibm Groovementioning
confidence: 99%
“…Recently, another study optimized XIAP-BIR2-selective benzazepinone[s8] screening and identified benzoxazepinone 40, a more potent BIR2-selective inhibitor with better in vivo pharmacokinetic properties. Benzoxazepinone 40 enhances mechanistically distinct apoptotic signaling compared to pan-IAP inhibitors [112]. Because Smac binds with XIAP leading to the induction of apoptotic cell death [44], various Smac mimetics have been developed to inhibit prosurvival function of XIAP, which could have significance in cancer therapy [113118].…”
Section: Introductionmentioning
confidence: 99%